(untitled) (PJDOL, 2023)
This research was aimed to explore the students’ attitude towards the use of mobile technology in distance education. The tool of research has been developed according to the standards of five-point Likert scale which is widespread and authentic for analyzing perception. It was also tested and validated through applying Chi Square for internal consistency. Using a survey method, data has been collected from the sample population comprised three hundred fifty five students and academics of Allama Iqbal Open University through the questionnaire.